Straw type governs methane-cycling microbiomes and CH4 emissions in paddy soils via abiotic and biotic interactions - Wang, Yanbo; Zhang, Yijia; Ji, Yang; Feng, Yanfang; Feng, Zhaozhong (Frontiers in Microbiology, 2026)
Straw incorporation is widely practiced in rice paddies to enhance soil fertility and crop yield, yet its effects on methane (CH4) emissions remain uncertain due to complex microbial and soil interactions. We conducted a soil column experiment with a no-straw control (CK) and amendments of rice (RS), wheat (WS), and maize (MS) straw. Seasonal CH4 fluxes, soil properties, CH4-cycling microbes, and abundances of mcrA and pmoA were analyzed across four rice growth stages. RS, WS, and MS significantly increased cumulative CH4 emissions by 15.7, 14.2, and 18.6 g m–2, respectively, with no significant differences among straw types. Soil pH significantly decreased under straw treatments, while rice grain yield significantly increased by 13.7–25.9%. Partial least squares path modeling (PLS-PM) analysis indicated that CH4 emissions were strongly negatively influenced by soil properties and microbial community composition. Among all the soil properties, the reduction in soil pH resulting from straw incorporation was the most significant factor increasing CH4 emissions. Microbial biomass carbon (MBC) contributed to CH4 emission variations, with its effect primarily driven by growth stage differences. Straw incorporation simultaneously stimulated a shift in the methanogenic toward Methanosarcinaceae and a shift in the methanotrophic toward Methylocystaceae. In contrast, the enhanced methane oxidation was insufficient to counterbalance the methanogenesis, causing increased net CH4 emissions. Although CH4 emissions were comparable among straw types, wheat straw achieved the largest (non-significant) yield increase, suggesting that wheat straw incorporation may offer a favorable balance between yield enhancement and CH4 emissions, warranting further field-based verification.